INOVASI PELAYANAN PUBLIK DI KOTA KREATIF DALAM MENINGKATKAN KEPERCAYAAN MASYARAKAT TERHADAP PEMERINTAH DI KOTA BANDUNG PROVINSI JAWA BARAT - Mesy Faridah Hendiyani (Institut Pemerintahan Dalam Negeri, 2019)
this article discusses public service innovations carried out by local governments to increase public trust in the government. The locus of this research is in the city of Bandung, West Java Province, one of the UNESCO creative city networks. The purpose of this paper is to analyze the innovation of public services carried out by the government to serve the public in creating and innovating so that public trust in the government increases. The research method uses a qualitative method with an inductive approach. Data obtained through interviews, observation and documentation. The results of this study indicate that the regional government of Bandung City creates service innovations in the form of facilities to support the creation and innovation of the community, although there are some things that still need to be addressed. The relationship between the government and the community is closer. The role of local government in serving the community to support the potential of community creation and innovation is very important. Keywords: community; creation; government; innovation; service